A Retrospective Study on the Efficacy of Two Different Rehabilitation Interventions on KOA: Shock Wave Therapy vs. Electroacupuncture Therapy. (29th November 2021) - Zhao, Yuhui; Wang, Xuebing; Zhang, Dianquan
Abstract : Objective . In this paper, we retrospectively reviewed the difference in clinical effectiveness of shock wave therapy and electroacupuncture therapy on knee osteoarthritis. Methods . A total of 128 treatment cases of knee osteoarthritis patients were extracted from the medical record system of Shenzhen Longhua District Central Hospital during the period from January 1, 2018, to January 30, 2020. The cases were divided into three groups for different treatments: shock wave group (n = 54 ), electroacupuncture group (n = 41 ), and control group (n = 33 ). The shock wave group was given shock wave therapy combined basis clinical treatment; meanwhile, the electroacupuncture group was given electroacupuncture on the basis of actual clinical treatment. The control group was given conventional topical nonsteroidal anti-inflammatory drugs (Voltaren). Osteoarthritis index scale, NRS scale, and WHOQOL-BREF were observed before treatment, after 2 weeks, and 4 weeks after treatment. Results . This study found that the osteoarthritis index scale and NRS scale of the shock wave group and the electroacupuncture group were lower than those before treatment; it had significant difference (P < 0.001 ). In WHOQOL-BREF, the shock wave group and the electroacupuncture group improved significantly four weeks after treatment (P < 0.001 ), which was statistically different from the conventional group (P = 0.04 ). Conclusion . Physical and rehabilitation medicine treatment (shock wave therapy) and traditional medical treatment (electroacupuncture) have better clinical effects on knee osteoarthritis, compared with conventional treatment. Shock wave and electric acupuncture have no apparent adverse reaction, suggesting that the treatment is safe and effective.